If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + 4y = 11120 Solving 1x + 4y = 11120 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 1x + 4y + -4y = 11120 + -4y Combine like terms: 4y + -4y = 0 1x + 0 = 11120 + -4y 1x = 11120 + -4y Divide each side by '1'. x = 11120 + -4y Simplifying x = 11120 + -4y
| 2-2v=v+64 | | x-11=90 | | 3x+y-z=1 | | 0.9375=x+0.25(3) | | 6x-2y-z=-14 | | f(x)=13x+52 | | 2lgx=2 | | (n+5)(p-14)=1400 | | 6y+2z=a+3y | | 2x+3y+z=1 | | 6y+2z=a+3fory | | 0=-5x^3+25x^3-17x | | 4x+3y=330 | | 10-5x=3x+6 | | -3(4p+4)-2(6-11p)=3(8+3p) | | 29+0.25p=59 | | 0.3x+0.4=0.28x+1.16 | | lny=7 | | 0.011x^3+22x-203=0 | | 14=2.50+2.30(m-1) | | E=f-g | | 2=18*3g | | 2(1-3x)=12 | | 3x+30+2x=360 | | 4x-1=-61 | | 108=-5(x-8)-(x+3) | | 28=2y | | 19.99n=80.96 | | F(x)=5x^2+3x+8 | | 3[2(x-1)-5]=4(x-4)+1 | | x^2-x-0.39=0 | | -23=-2(2b-1) |